Perancangan Sistem Informasi Mahasiswa Pelajar Papua Dalam Aplikasi Visual Basis Dan Database SQL Server - Bagas Santoso; Maulana Fikri (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2023)
The rapid development of information and communication technology is beneficial to all areas of life, where through information technology the process of collecting, processing data to presenting information becomes very fast, precise and accurate. This development makes computer science an integral part of human life. Computers are generally used for processing data to produce information. With the many conveniences that can be obtained by using this computerized system, not a few organizations have implemented this computerized system. Computer systems enable organizations to manage large amounts of data and information, thereby of course helping organizations make decisions quickly and accurately in determining organizational strategies and policies. The current development of information technology also makes competition between institutions in terms of service quality an added value in attracting the interest of all stakeholders because transparency, accountability and quality of information will be more effective and efficient.